The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/6860432
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immunotherapy in Extensive Stage Small-Cell Lung Cancer: A Review of the Literature

Abstract: Lung cancer is the second most common cancer in both sexes worldwide. Small-cell lung cancer (SCLC) is a form of neuroendocrine tumor, which is classified into limited and extensive-stage disease and shows excellent initial response to chemotherapy; however, almost all patients relapse later. During the past few years, several clinical trials have evaluated the effect of addition of immunotherapy to conventional chemotherapy in patients with extensive SCLC. Checkpoint inhibitors are currently under investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…Due to the rapid progression and quite invasive nature, approximately 70% of SCLC patients are advanced stage at the time of initial diagnosis [ 3 ]. Platinum-based chemotherapy is the first-line treatment for patients with ED-SCLC [ 4 , 7 ]. SCLC cells respond to this treatment initially, but over the course of treatment, they acquire resistance to treatment, and most patients relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rapid progression and quite invasive nature, approximately 70% of SCLC patients are advanced stage at the time of initial diagnosis [ 3 ]. Platinum-based chemotherapy is the first-line treatment for patients with ED-SCLC [ 4 , 7 ]. SCLC cells respond to this treatment initially, but over the course of treatment, they acquire resistance to treatment, and most patients relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based chemotherapy is used as the initial treatment for patients with ED-SCLC, and it has improved survival [ 4 ]. A clinical feature of SCLC is that it responds efficiently to treatment initially but then acquire drug resistance during treatment [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to SCLC, nivolumab was also tested for pretreated patients with SCLC in the CheckMate-032 trial, obtaining approval from the FDA. This trial showed an objective response rate (ORR) of 10% with nivolumab and 23% with nivolumab + ipilimumab, with grade 3–4 adverse effects of 14% and 33%, respectively [ 74 ]. Soon after, the addition of atezolizumab (anti-PD-L1) to CT in the first-line SCLC treatment in the IMpower133 trial achieved the first OS improvement in decades [ 70 ].…”
Section: Impact Of Immunotherapy On the Survival Of Patients Withmentioning
confidence: 99%
“…A similar reduction in the death risk was also identified in the phase II CASPIAN trial, which included the PD-L1 inhibitor durvalumab in combination with CT [ 71 ]. Thanks to the results of the KEYNOTE-028 and KEYNOTE-158 trials, the FDA approved in 2019 the use of pembrolizumab as monotherapy for patients with metastatic SCLC with disease progression on or after platinum-based CT and at least one other prior line of therapy [ 74 ].…”
Section: Impact Of Immunotherapy On the Survival Of Patients Withmentioning
confidence: 99%
See 1 more Smart Citation